Implementasi Media Audio-Visual Dalam Pembelajaran IPAS Kelas IV di MIM Bandingan Kecamatan Kejobong Kabupaten Purbalingga - Vera Regina Azaria; Abu Dharin (JURNAL ILMIAH NUSANTARA, 2026)
The use of technology-based learning media has become an important requirement in improving the quality of the learning process, including in science education at MI Muhammadiyah Bandingan, which has implemented audio-visual media to support the delivery of material. This study aims to analyze the implementation of audio-visual media in IPAS learning in grade IV and to identify the supporting and inhibiting factors in its implementation. The study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The result show that MI Muhammdiyah Bandingan has implemented audio-visual media in IPAS learning in grade IV quite well. The implementation was carried out in three stages, namely planning, which included the preparation of teaching modules, materials, learning tools, and evaluation instruments, implementation, which included introductory, core, and closing activities using videos and powerppoint presentations to improve student understanding, and evaluation, which was carried out through the assessment of attitudes, knowledge, and skills. Supporting factors for this media include the availability of school facilities, student enthusiasm, and the ease with which teachers can deliver material, while inhibiliting factors include technical constraints such as power outages, limited media content, and the potential for noise disturbance between classes.